Nickel in Soil Modifies Sensitivity to Diazinon Measured by the Activity of Acetylcholinesterase, Catalase, and Glutathione S-Transferase in Earthworm Eisenia fetida - Agnieszka Zawisza-Raszka; Bogdan Dolezych (Applied and Environmental Soil Science)
Nickel in typical soils is present in a very low concentration, but in the contaminated soils it occurs in locally elevated concentrations. The aim of this study was to examine the effect of nickel in the concentrations of 300 (very high, close to LOEC for reproduction) and 900 (extremely high, close to LOEC for mortality) mg/kg dry soil on the life history and acetylcholinesterase, catalase, and glutathione S-transferase activities in earthworm Eisenia fetida and to establish how nickel modifies the sensitivity to organophosphorous pesticide—diazinon. Cocoons production and juveniles’ number were significantly lower only in groups exposed to Ni in the concentration of 900 mg/kg dry soil for two months. Diazinon administration diminished the AChE activity in the GI tract and in the body wall. The interaction between diazinon and nickel was observed, and, in consequence, the AChE activity after the pesticide treatment was similar to controls in worms preexposed to nickel. Both pesticide administration and exposure to nickel caused an increase in the GST activity in examined organs and CAT activity in body wall. Both biometric and development data and simple enzymatic analysis, especially the AChE and GST, show a Ni pretreatment effect on the subsequent susceptibility to pesticide.